The Prospects and Effects of Unconventional Oil and Gas Exploitation Activities - Novia Sekarsari; Ibrahim Sertçelik (Indonesian Student Association Study Center in Türkiye, 2025)
Unconventional hydrocarbons are hydrocarbon sources located in zones different from those typically associated with conventional hydrocarbon accumulations. This alternative energy resource, originating primarily from the United States and Russia, has begunto attract attention and development efforts in Indonesia. One of the Indonesian regions with potential for unconventional hydrocarbons especially shale gas is the North East Java Basin. However, several environmental issues must be considered in unconventional oil and gas exploitation activities. These include impacts on surface water and groundwater, air resources, as well as waste management and disposal problems. Therefore, alongside the advancement of technologies for unconventional oil and gas exploitation, it is essential to develop environmentally sustainable technologies that can address these challenges. This article discusses the role of geophysics in assessing both the potential and limitations of its application in resolving environmental problems, particularly those related to land and inland water environments